Digital tasks and ICT capital: Methodologies and data - Lorenz Gschwent; Dario Guarascio; Stefan Jestl; Alireza Sabouniha; Roman Stöllinger (The Vienna Institute for International Economic Studies (wiiw), 2023)
This report describes the data and documents the data collection and adjustment procedures for a project called 'Comparative Advantage in the Digital Era'. This project uses granular information on the tasks being performed by workers in different occupations on the one hand and different asset types of capital on the other hand to pin down comparative advantages in digital tasks and ICT capital. Given the nature of the project, the data work focuses on the adjustment of the underlying occupation and industry-specific employment data and the asset-type and industry-specific capital stock data to match the figures in the Intern-Country Input Output tables. The latter are a key ingredient for the calculation of endowment based comparative advantages. Finally, it explains the Survey on Italian Occupations (Indagine Campionaria sulle Professioni, ICP), a unique database on the characteristics of occupations in the Italian and its US-American counterpart, the O*NET database. The data work documented in this report builds the foundation for the further work of the aforementioned project.
Keywords: C80; 330; Employment; capital stocks; digital tasks; ICT capital